Depression and Dementia - Volicer Ladislav; Vaňková Hana (Journal of Depression And Therapy, 2016)
Relationship between dementia is very complex and individual. There are some pathogenetic processes that may be common to both conditions: neurotransmitter deficits, vascular changes and beta amyloid deposits. Presence of depression in persons with dementia have serious consequences on progression of dementia, quality of life and behavioral symptoms of dementia. Therefore, it is important to treat effectively even minor depressive symptoms.
Keywords: Depression